2016
DOI: 10.21577/0100-4042.20160152
|View full text |Cite
|
Sign up to set email alerts
|

A new Rhodamine B derivative RBMAB as a highly selective and sensitive chemosensor for Fe3+ with low detection limit

Abstract: A new Rhodamine B derivative RBMAB, namely 3-amino-N-(2-(3',6'-bis (diethylamino)-3-oxospiro[isoindoline-1,9'-xanthen]-2-yl) ethyl)benzamide, was designed, synthesized and structurally characterized to develop a chemosensor. The studies show that RBMAB exhibits high selectivity toward Fe 3+ among many other metal cations in an ethanol-H 2 O (3:2, v/v, PBS buffer, 1.2 mmol L -1 , pH 7.2) solution. It has a low detection limit of 0.021μm. Fluorescence microscopy experiments further demonstrate that RBMAB can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…When pH was adjusted to between 1 and 5, the fluorescence intensity of the PTRH was reputedly enhanced due to spirolactam ring opening in the amide form of rhodamine. These results clearly indicated that the PTRH sensor was insensitive to pH ranging from 5 to 14 and may work under approximately physiological conditions with very low background fluorescence …”
Section: Resultssupporting
confidence: 90%
“…When pH was adjusted to between 1 and 5, the fluorescence intensity of the PTRH was reputedly enhanced due to spirolactam ring opening in the amide form of rhodamine. These results clearly indicated that the PTRH sensor was insensitive to pH ranging from 5 to 14 and may work under approximately physiological conditions with very low background fluorescence …”
Section: Resultssupporting
confidence: 90%
“…To demonstrate facile functionalization of the obtained hydrogel to provide a pH‐ and metal ion–sensing platform, a rhodamine derivative (RHB‐NH 2 ) was chosen. It is well established that the rhodamine moiety exhibits colorimetric response to acidic pH, as well as toward certain metal ions like Fe 3+ . This is easily observable by naked eye, as well as through UV–vis spectroscopy.…”
Section: Resultsmentioning
confidence: 98%
“…It is well established that the rhodamine moiety exhibits colorimetric response to acidic pH, as well as toward certain metal ions like Fe 3+ . [39][40][41][42][43][44][45][46] This is easily observable by naked eye, as well as through UV-vis spectroscopy. The spectra of RHB-NH 2 taken at pH 3.3 (in acetate buffer) and pH 7.4 (phosphate buffer) shows a strong absorbance peak at 561 nm only at acidic pH ( Figure S7, Supporting Information).…”
Section: Functionalization Of Hydrogels For Sensing Applicationsmentioning
confidence: 99%